Settlement of Sale and Purchase Underhand Where the Seller's Whereabouts Are Unknown - Istriany, Andy Rahmayanti Prihatining (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2024)
The purpose of this study is to find out and analyze the anticipation of the problem of underhand buying and selling where the seller's whereabouts are unknown. To find out and analyze the settlement of underhand buying and selling where the seller's whereabouts are unknown. The approach method used by the researcher is the case approach and the statutory approach. This type of research is normative law. The sources and types of data in this study are secondary data obtained from literature studies. Based on the results of the study that anticipating the problem of underhand buying and selling where the seller's whereabouts are unknown is that in making a sale and purchase agreement, they must adhere to the principle of good faith. The buyer must also meet the requirements required in carrying out the sale and purchase of land up to the name change process. Thus, if all these requirements are met, the land sale and purchase process up to the certificate name change process can run smoothly without any obstacles. Settlement of Underhand Buying and Selling Where the Seller's Whereabouts Are Unknown is to initiate and resolve civil disputes that occur between the Plaintiff and the Defendant, one of the disputing parties must submit a request for examination (file a lawsuit) to the court. The parties whose rights have been violated in a civil case are called plaintiffs who file a lawsuit with the court and address it to the party who violated it (defendant) by stating the case (posita) and accompanying it with what the plaintiff demands (petitum).